The Evolution of Tarsal Adhesive Microstructures in Stick and Leaf Insects (Phasmatodea) - Büscher, Thies H.; Buckley, Thomas R.; Grohmann, Constanze; Gorb, Stanislav N.; Bradler, Sven (Frontiers in Ecology and Evolution, 2018)
Insects have developed specialized structures on their feet for adhering to surfaces, with stick and leaf insects or Phasmatodea exhibiting an unexpectedly high diversity of these structures. In Phasmatodea, attachment on different substrates is achieved by two types of pads on the legs: the euplantulae on the tarsomeres and the arolium on the pretarsus. The euplantulae are adhesive structures capable of adaptability to the substrate profile and generation of the required attachment strength. The diversity of euplantular microstructures of 56 species that represent all major lineages recognized within Phasmatodea and the whole biogeographical distribution of the group are examined using scanning electron microscopy (SEM). Nine different types of attachment structures can be distinguished whereby one, the nubby type, can be further divided into three different distinct types based on the specific ratio of each conical outgrowth. We mapped the morphological data from the SEM onto a phylogenetic tree we that reconstructed based on molecular data. Previously, the evolution of different adhesive microstructures (AMs) on these pads has been suggested to reflect phylogenetic groups. However, different types of AMs are found within monophyletic groups, and our ancestral character state reconstruction suggests smooth euplantulae in the ground pattern of Euphasmatodea and multiple independent origins of other forms. The type of AM appears to be strongly associated with ecomorphs, e.g., smooth euplantular surfaces are more frequently found in tree-dwellers than in ground-dwellers, whilst the attachment pads of ground-dwelling species primarily bear conical cuticular outgrowths (nubby euplantulae).